Dictionary of Public Policy - Howlett, Michael, 1955- (UK: USA: Edward Elgar Publishing, 2022)
"This authoritative Dictionary provides comprehensive definitions of key terms in public policy. Unpacking the increasingly complex and diffusive world of public policy, it offers an exhaustive definitional guide to the terminology utilised by contemporary policy scholars. Prepared by a team of expert scholars, entries summarise the social, political and economic contexts of fundamental public policy vocabulary and dissect its usage in modern scholarship. Entries are meticulously cross-referenced to guarantee accessibility and illuminate a broad yet detailed understanding of topics. Providing recommendations for further reading, it features 330 carefully defined entries to aid researchers investigating both novel and historical approaches to public policy. Assembling a broad overview of the discipline, this Dictionary is a useful reference book for students at all levels and early-career researchers. It will also benefit policy practitioners looking for a superior understanding of the crucial vocabulary that governs their field"--
Includes bibliographical references (pages 237-265) and indexes.
Keywords: Political planning -- Dictionaries